A kind of sea urchin-shaped vanadium nitride nanoparticle and preparation method thereof

By hydrothermal synthesis of high-active amorphous vanadium oxide precursor and nitriding at low temperature, sea urchin-like vanadium nitride nanoparticles were prepared, which solved the problems of slow reaction kinetics and insufficient rate performance of the negative electrode materials of traditional lithium-ion batteries, and achieved high efficiency Lithium ion transport and electrochemical performance improvements.

CN118970038BActive Publication Date: 2025-02-14XINXIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411441342.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-02-14
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The slow reaction kinetics and low operating voltage of traditional graphite negative electrode materials hinder the fast charging capability of lithium-ion batteries, and the inherent low conductivity of VN and moderate Li+ diffusion rate affect their capacity release and rate performance.

Method used

The cheap V2O5 is used to prepare highly active amorphous vanadium oxide precursors through hydrothermal strategies, and nitrides under an ammonia atmosphere to synthesize sea urchin-like vanadium nitride nanoparticles.

Benefits of technology

By improving the reactivity and structural advantages, the reaction kinetics and rate performance of the negative electrode material of lithium-ion battery is significantly improved, and long cycle life, high safety and high power density are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118970038B_ABST
    Figure CN118970038B_ABST
Patent Text Reader

Abstract

The present invention discloses a sea urchin-shaped vanadium nitride nanoparticle and a preparation method thereof, belonging to the technical field of nanomaterials. Using V2O5 as a vanadium source, ammonia water as a pH regulator, and a hydrogen peroxide solution as an oxidant, a highly active amorphous vanadium oxide precursor is synthesized by hydrothermal method, and low-temperature nitridation is performed in an ammonia atmosphere to form porous sea urchin-shaped VN nanoparticles with a high specific surface area. The pore size distribution shows that the material has a large number of mesopores, and the electrochemical performance test is carried out using the nitridation product as a negative electrode material for a lithium ion battery. The amorphous vanadium oxide precursor described in the present invention has the characteristics of high activity, and the low-temperature nitridation product has a high specific surface area of ​​50 mA g ‑1 The specific capacity is 287 mAh g after 400 cycles at the current density ‑1 , and 1000 mA g ‑1 After 2000 cycles at the same rate, the specific capacity is 150 mAh g ‑1 The urchin-shaped VN nanoparticles are expected to become a new type of lithium storage material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanomaterials, and in particular to a sea urchin-shaped vanadium nitride nanoparticle and a preparation method thereof. Background Art

[0002] With the increasing popularity of electric vehicles, there is a higher demand for high-power, long-life and high-safety lithium-ion batteries. However, the slow reaction kinetics and low operating voltage of traditional graphite anodes hinder the fast charging capability of the battery. Therefore, the development of anode materials with high lithium-ion diffusion rates and fast reaction kinetics has attracted much attention. VN has excellent electronic conductivity and chemical stability, making it an ideal choice for advanced anode materials with long cycle life, high safety and high power density. However, the inherent low conductivity and moderate Li + The diffusion rate affects its capacity release and rate performance. The intrinsic electrochemical reaction rate of VN is subject to the reaction activation energy, which is determined by its initial state structure. However, the initial state structure of VN depends largely on the composition and structure of the vanadium oxide precursor.

[0003] In the synthesis process of VN, vanadium oxide precursors (such as organic vanadium sources, vanadium-based oxides, etc.), reaction temperature, reaction time, etc. all significantly affect the structure and electrochemical properties of VN. Vanadium oxide precursors are one of the commonly used vanadium source precursors due to their special advantages. Previous studies have not noticed the great influence of the components and structures of vanadium oxide precursors on the products. Vanadium oxide precursors with different components and structures have different reactivity in the entire reaction system, thus showing different growth behaviors, and finally obtaining VN materials with different structures. Compared with crystals, amorphous vanadium oxides are active species with lower reaction energy barriers, with the characteristics of "long-range disorder and short-range order", which are easy to expose more reactive sites, and their own phase transformation is relatively easy. In the chemical reaction process of the system, the reaction activity can be improved to achieve the goal of reducing the reaction temperature, shortening the reaction time and preparing VN materials with excellent structures. However, the preparation of VN materials with highly reactive precursors is still in its early stages and requires further in-depth research. Therefore, it is of great significance to find a low-cost vanadium source and further study the components and structures of highly active amorphous vanadium oxide precursors for the synthesis of VN with excellent structures.

[0004] Based on this, we used low-cost V2O5 to prepare highly active amorphous vanadium oxide precursors through a hydrothermal strategy. The precursors were endowed with a large number of active H2O and OH functional groups, and the long-range disordered structure reduced its reaction energy barrier, thereby improving the reaction activity. Urchin-like VN nanoparticles were synthesized using amorphous vanadium oxide as a vanadium source precursor through an in-situ low-temperature nitridation strategy, clarifying the structure-activity relationship between structural characteristics and rate performance. Summary of the invention

[0005] In order to deeply understand the in-situ low-temperature nitridation process of high-activity amorphous vanadium oxide precursor and the relationship between structure and performance, the purpose of the present invention is to provide a high-activity amorphous vanadium oxide precursor and an in-situ low-temperature nitridation product and application.

[0006] The present invention discloses a sea urchin-shaped vanadium nitride nanoparticle, wherein the crystallographic data of the vanadium nitride nanoparticle is a = 4.139(3) Å, b = 4.139(3) Å, c =4.139(6) Å, α = 90.000(0)˚, β = 90.000 (0)˚, γ = 90.000(0)˚, V = 70.91(3) Å 3 , Z = 4, cubic system, Fm-3m space group.

[0007] The present invention discloses a method for preparing the above-mentioned sea urchin-shaped vanadium nitride nanoparticles, comprising the following steps: (1) using V2O5 as a vanadium source, ammonia water as a pH regulator, and a hydrogen peroxide solution as an oxidant to hydrothermally synthesize a highly active amorphous vanadium oxide precursor; and (2) nitriding the amorphous vanadium oxide precursor at low temperature in an ammonia atmosphere to form the porous sea urchin-shaped vanadium nitride nanoparticles.

[0008] Furthermore, the amorphous vanadium oxide precursor contains H2O and OH. The highly active amorphous vanadium oxide precursor of the present invention contains a large amount of H2O and OH functional groups, which can improve the reaction activity and reduce the reaction energy barrier during the chemical reaction of the system.

[0009] Furthermore, the specific process of preparing the amorphous vanadium oxide precursor in step (1) is as follows: (1) weighing 0.45-0.55 g of V2O5 and dispersing it into 20-30 mL of deionized water, adding dropwise 15-20 mL of ammonia water, and magnetically stirring for 30-50 minutes to prepare solution A;

[0010] (2) Add 20-30 mL of 30% hydrogen peroxide solution to solution A and stir magnetically for 6-7 hours to prepare solution B;

[0011] (3) Take 60-80 mL of ethanol and add it dropwise to solution B. Stir thoroughly to prepare solution C.

[0012] (4) Solution C was transferred into a 200 mL polytetrafluoroethylene reactor for hydrothermal reaction at 90° C.-110° C. for 600-800 minutes. The obtained product was washed with deionized water and ethanol, vacuum filtered, and dried at 60° C. to obtain the amorphous vanadium oxide precursor.

[0013] Furthermore, the specific operation of step (2) is: heating the highly active amorphous vanadium oxide precursor to 400-500° C. in a tube furnace and maintaining it for 2-4 hours, and performing in-situ low-temperature nitridation in an ammonia atmosphere to obtain the sea urchin-shaped vanadium nitride nanoparticles.

[0014] The present invention provides a high-performance lithium-ion battery, wherein the negative electrode material of the battery is made of the above-mentioned sea urchin-shaped vanadium nitride nanoparticles.

[0015] Furthermore, the battery is -1 The specific capacity is 287 mAh g after 400 cycles at the current density -1 , and 1000 mA g -1 After 2000 cycles at the same rate, the specific capacity is 150 mAh g -1 .

[0016] Advantageous Effects of the Invention

[0017] 1. A highly active amorphous vanadium oxide precursor was prepared by hydrothermal strategy using low-cost V2O5. During the low-temperature in-situ nitridation process, the disordered vanadium oxygen complex was transformed into the corresponding nanoscale porous sea urchin-like vanadium nitride. The porous structure is conducive to the contact between the electrolyte and the active material. The nanostructure can effectively shorten the lithium ion transmission path and significantly improve the transmission dynamics of ions and electrons. It can also buffer the volume changes caused by the lithium insertion and de-lithiation process.

[0018] 2. The highly active amorphous vanadium oxide precursor prepared by the present invention carries a large number of H2O and OH functional groups, whose removal will locally release a large amount of heat, and the amorphous loose structure and the basic unit with low reaction energy barrier greatly promote the Li + The diffusion and migration in the bulk phase show high reactivity and special growth behavior. The unique high-activity structure makes it show a special in-situ low-temperature nitridation process during heat treatment. The electrochemical performance test of the nitridation product as a negative electrode material for lithium-ion batteries shows that: at 50 mA g -1 The specific capacity is 287 mAh g after 400 cycles at the current density -1 Around, and 1000 mA g -1 After 2000 cycles at the same rate, the specific capacity is 150 mAh g -1 about.

[0019] 3. The present invention found that the high specific surface area porous sea urchin-like VN prepared by highly active amorphous vanadium oxide is conducive to the contact between the electrolyte and the active material, promoting the Li + The desolvation of Li + It provides more diffusion channels and active sites. This unique structure can obviously improve the transport kinetics of ions and electrons, thereby showing excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the XRD pattern of the highly active amorphous vanadium oxide precursor prepared in Example 1;

[0021] Figure 2 TG graph of the highly active amorphous vanadium oxide precursor prepared in Example 1;

[0022] Figure 3 The XRD pattern of the low temperature nitridation product prepared in Example 1;

[0023] Figure 4 This is the pore size distribution diagram of the low temperature nitridation product prepared in Example 1;

[0024] Figure 5 The N2 adsorption-desorption isotherm curve of the low-temperature nitridation product prepared in Example 1;

[0025] Figure 6 This is a SEM image of the low temperature nitridation product prepared in Example 1;

[0026] Figure 7 The low-temperature nitridation product prepared in Example 1 was assembled into a battery at 50 mA g -1 Cycling performance diagram under current density;

[0027] Figure 8 The rate performance diagram at different current densities after the low-temperature nitridation product prepared in Example 1 is assembled into a battery;

[0028] Fig. 9 The low-temperature nitridation product prepared in Example 1 was assembled into a battery and then charged at 1000 mA g -1 Cycling performance diagram under current density;

[0029] Fig.10 is the pore size distribution diagram of the nitrided product prepared in the comparative example;

[0030] Fig.11 It is the N2 adsorption-desorption isotherm curve of the nitridation product prepared in the comparative example;

[0031] Fig.12 is the SEM image of the nitrided product prepared in the comparative example;

[0032] Fig.13 The nitrided product prepared in the comparative example was assembled into a battery and then charged at 50 mA g -1 Cycling performance diagram under current density;

[0033] Fig.14 The figure is a rate performance diagram at different current densities after the nitridation product prepared in the comparative example is assembled into a battery. DETAILED DESCRIPTION

[0034] The present invention is described in detail below by way of examples. Example 1

[0035] Weigh 0.45 g of V2O5 and disperse it in 20 mL of deionized water in a 200 mL beaker, add 15 mL of ammonia water dropwise, stir magnetically for 30 minutes to dissolve, and prepare solution A.

[0036] Measure 20 mL of 30% hydrogen peroxide solution and add it to solution A. Stir magnetically for 6 hours to prepare solution B.

[0037] Measure 60 mL of ethanol and add dropwise to solution B. Stir thoroughly for 10 minutes to prepare solution C.

[0038] Solution C was transferred into a 200 mL polytetrafluoroethylene reactor for hydrothermal reaction at 90°C for 600 minutes. The obtained product was washed with deionized water and ethanol, vacuum filtered, and dried at 60°C to obtain a highly active amorphous vanadium oxide precursor.

[0039] The X-ray powder diffraction test of the high-activity vanadium oxide precursor powder obtained in this example shows that the high-activity vanadium oxide has no obvious characteristic diffraction peaks and presents an amorphous structure, such as Figure 1 shown.

[0040] The highly active vanadium oxide precursor of the present invention contains a large amount of OH and H2O functional groups, such as Figure 2 As shown. Figure 2 It can be seen from the TG that the temperature from room temperature to 196°C mainly comes from some adsorbed water or structural water on the surface, and 196-380°C corresponds to the hydroxyl groups inside the material. The precursor has two obvious weight loss stages, indicating that the products carrying OH and H2O react violently in this process, and a large amount of heat is released locally to accelerate the reaction rate of the system. The loss of these small molecular components of the precursor and the complete amorphous structure greatly reduce the reaction temperature range and improve the reaction activity.

[0041] The present invention performs in-situ nitridation on a highly active vanadium oxide precursor in a tubular furnace at a temperature of 400° C. for 4 hours in an ammonia atmosphere, and the obtained nitridation product is the sea urchin-shaped vanadium nitride nanoparticles prepared by the present invention.

[0042] from Figure 3 It can be seen from XRD that the low-temperature nitridation product is a VN material with good crystallinity.

[0043] The pore structure of porous VN materials was studied using N2 adsorption-desorption isotherms. Figure 4 As shown in Figure 2, the isotherm curve shows a typical Langmuir IV hysteresis, proving the existence of a mesoporous structure with an average pore size of about 4 nm. The mesoporous structure is formed by the accumulation of nanoparticles. Further calculations show that the BET specific surface area is 688 m 2 g -1 ,like Figure 5 As shown, such a mesoporous structure is beneficial to reducing the volume change during the cycle and improving the rate performance of lithium ions.

[0044] The morphology characteristics of the low temperature nitridation product prepared in Example 1 were analyzed using a scanning electron microscope (SEM). Figure 6 shown. Figure 6 The VN material was shown to form a uniform urchin-like three-dimensional structure through self-assembly. The urchin-like three-dimensional structure is composed of loose nanowires, which gather together at one end to form a center and radiate from the other end. This structure can form channels that are conducive to the insertion and removal of lithium ions, thereby shortening the diffusion path of lithium ions.

[0045] Electrochemical performance tests show that ( Figure 7 , Figure 8 and Fig. 9 ), sea urchin-shaped vanadium nitride nanoparticles prepared at low temperature as negative electrode materials for lithium-ion batteries have a voltage window of 0.01-3.0 V (vs. Li / Li + ) has excellent long cycle performance and good high rate performance at 50 mA g -1 The specific capacity is 287 mAh g after 400 cycles at the current density -1 Around, and 1000 mA g -1 After 2000 cycles at the same rate, the specific capacity is 150 mAh g -1 about. Example 2

[0046] Weigh 0.50 g of V2O5 and disperse it in 25 mL of deionized water in a 200 mL beaker, add 17 mL of ammonia water dropwise, stir magnetically for 40 minutes to dissolve, and prepare solution A.

[0047] Measure 25 mL of 30% hydrogen peroxide solution and add it to solution A. Stir magnetically for 6.5 hours to prepare solution B.

[0048] Measure 70 mL of ethanol and add dropwise to solution B, stir thoroughly to prepare solution C.

[0049] Solution C was transferred into a 200 mL polytetrafluoroethylene reactor for hydrothermal reaction at 100°C for 700 minutes. The obtained product was washed with deionized water and ethanol, vacuum filtered, and dried at 60°C to obtain a highly active amorphous vanadium oxide precursor.

[0050] The highly active vanadium oxide precursor was in-situ nitrided in an ammonia atmosphere at a temperature of 450° C. for 3 hours in a tube furnace to obtain a nitrided product.

[0051] The characterizations of the high-activity vanadium oxide precursor and the low-temperature nitridation product are the same as those in Example 1. Example 3

[0052] Weigh 0.55 g of V2O5 and disperse it in 30 mL of deionized water in a 200 mL beaker, add 20 mL of ammonia water dropwise, stir magnetically for 50 minutes to dissolve, and prepare solution A.

[0053] Measure 30 mL of 30% hydrogen peroxide solution and add it to solution A. Stir magnetically for 7 h to prepare solution B.

[0054] Measure 80 mL of ethanol and add dropwise to solution B, stir thoroughly to prepare solution C.

[0055] Solution C was transferred into a 200 mL polytetrafluoroethylene reactor for hydrothermal reaction at 110° C. for 800 minutes. The obtained product was washed with deionized water and ethanol, vacuum filtered, and dried at 60° C. to obtain a highly active amorphous vanadium oxide precursor.

[0056] The high-activity vanadium oxide precursor was subjected to in-situ low-temperature nitridation in an ammonia atmosphere at a temperature of 500°C for 2 hours in a tube furnace to obtain a nitrided product.

[0057] The characterizations of the high-activity vanadium oxide precursor and the low-temperature nitridation product are the same as those in Example 1. Comparative Example

[0058] This comparative example provides a vanadium nitride particle, which is composed of vanadium nitride nanoparticles. The vanadium nitride particles have an irregular shape. The preparation method is the same as Example 1, except that a highly active amorphous vanadium oxide precursor is heated to 500°C-1000°C in a tube furnace and subjected to high-temperature nitridation in an ammonia atmosphere (i.e., the difference from Example 1 is the nitridation temperature). Fig.10 The pore size distribution diagram of the nitrided product prepared in the comparative example shows that there is no obvious pore structure. Fig.11 The N2 adsorption-desorption isotherm curve shows that the specific surface area is only 56 m2 g -1 . Fig.12 The SEM image shows that the nanoparticles have irregular morphology, not sea urchin-like morphology.

[0059] Electrochemical performance tests show that ( Fig.13 and Fig.14 ), vanadium nitride particles as negative electrode materials for lithium-ion batteries have a voltage window of 0.01-3.0 V (vs. Li / Li + ), 50 mA g -1 After 400 cycles at the current density, the specific capacity is only 30 mAh g -1 Around, and 1000 mA g -1 The specific capacity is only 3 mAh g at the current rate. -1 about.

[0060] It can be seen from Examples 1-3 and the comparative example that the method for preparing porous sea urchin-shaped vanadium nitride nanoparticles in the example adopts V2O5 as a vanadium source, ammonia water as a pH regulator, and a hydrogen peroxide solution as an oxidant, and synthesizes a highly active amorphous vanadium oxide precursor by hydrothermal method, and nitridates it at low temperature (400°C-500°C) in an ammonia atmosphere to form porous sea urchin-shaped VN nanoparticles with high specific surface area. Compared with the nitridation method of preparing vanadium nitride at high temperature (500°C-1000°C) in an ammonia atmosphere in the comparative example, the porous sea urchin-shaped vanadium nitride nanoparticles with high specific surface area are prepared in the example, and the size is uniform, and the specific surface area is 688 m 2 g -1 , while the comparative example cannot obtain a porous urchin-like VN structure with a high specific surface area. The main reason is that: at the beginning, the surface energy of the primary particles is relatively large, and the primary particles are easy to agglomerate together to form microspheres in order to reduce the surface energy. As the reaction proceeds, the reaction rate of the vanadium oxide is controlled. At a slower reaction rate, each primary particle grows anisotropically and gradually grows into nanowires. Finally, the nanospheres composed of primary particles grow into highly active urchin-like vanadium oxides with a porous structure. Low-temperature in-situ nitridation can maintain the urchin-like morphology of the nanoporous structure, while high-temperature nitridation treatment will destroy the surface nanowire morphology, resulting in an increase in pore size and a decrease in specific surface area, thereby reducing the interface area and active sites, and failing to shorten the diffusion channel of ions in the electrode, which is not conducive to the insertion / extraction of lithium ions, and ultimately affecting the electrochemical performance.

[0061] Moreover, the size distribution of vanadium nitride in the comparative example is uneven, and the specific surface area of ​​the comparative example is only 56 m 2 g -1 , and there is no obvious pore size distribution. In addition, the urchin-like vanadium nitride nanoparticles prepared at low temperature as the negative electrode material of lithium-ion batteries have a high conductivity at 50 mA g -1The specific capacity is 287 mAh g after 400 cycles at the current density -1 Around, and 1000 mA g -1 After 2000 cycles at the same rate, the specific capacity is 150 mAh g -1 In the comparative example, the vanadium nitride particles are about 50 mA g -1 After 400 cycles at the same current density, the specific capacity is only 30 mAh g -1 Around, and 1000 mA g -1 The specific capacity is only 3 mAh g at the current rate. -1 This shows that the preparation method of the porous sea urchin-shaped vanadium nitride provided by the present invention can produce sea urchin-shaped nanoparticles with uniform size and high specific surface area, which can be well used as a new lithium-ion battery material.

Claims

1. A method for preparing sea urchin-shaped vanadium nitride nanoparticles, characterized in that: The crystallographic data of the vanadium nitride nanoparticles are a = 4.139(3) Å, b = 4.139(3) Å, c =4.139(6) Å, α = 90.000(0)˚, β = 90.000(0)˚, γ = 90.000(0)˚, V = 70.91(3) Å 3 , Z = 4, cubic system, Fm-3m space group, the preparation method of the vanadium nitride nanoparticles comprises the following steps: (1) using V2O5 as a vanadium source, ammonia water as a pH regulator, and a hydrogen peroxide solution as an oxidant to synthesize a highly active amorphous vanadium oxide precursor by hydrothermal method; (2) subjecting the amorphous vanadium oxide precursor to low-temperature nitridation in an ammonia atmosphere to form porous sea urchin-shaped vanadium nitride nanoparticles; the specific operation of the step (2) is as follows: heating the highly active amorphous vanadium oxide precursor to 400-500°C in a tube furnace and maintaining it for 2-4 hours, and subjecting it to in-situ low-temperature nitridation in an ammonia atmosphere to obtain the sea urchin-shaped vanadium nitride nanoparticles; the amorphous vanadium oxide precursor contains H2O and OH functional groups.

2. The method for preparing sea urchin-shaped vanadium nitride nanoparticles according to claim 1, characterized in that: The specific process of preparing the amorphous vanadium oxide precursor in step (1) is as follows: (1) weighing 0.45-0.55 g of V2O5 and dispersing it into 20-30 mL of deionized water, adding dropwise 15-20 mL of ammonia water, and stirring magnetically for 30-50 minutes to prepare solution A; (2) Add 20-30 mL of 30% hydrogen peroxide solution to solution A and stir magnetically for 6-7 hours to prepare solution B; (3) Take 60-80 mL of ethanol and add it dropwise to solution B. Stir thoroughly to prepare solution C. (4) Solution C was transferred into a 200 mL polytetrafluoroethylene reactor for hydrothermal reaction at 90° C.-110° C. for 600-800 minutes. The obtained product was washed with deionized water and ethanol, vacuum filtered, and dried at 60° C. to obtain the amorphous vanadium oxide precursor.